(untitled) (Journal of Interdisciplinary Insights, 2023)
Hybrid warfare, as a new form of modern conflict, reflects the complex changes in the international security environment. Within the framework of hybrid warfare, Russia’s private military companies, particularly the Wagner Group, play a significant role in global conflicts. This paper employs post-positivist, deductive methodologies and literature review approaches to study the formation and development of the Wagner Group. It concludes that Wagner is an integral part of Russia’s hybrid warfare strategy and reflects a shift in global military intervention strategies. By analyzing the organizational structure of the Wagner Group, the scope of its activities, and its specific actions in places such as Ukraine and Syria, this paper examines the group’s indirect realization of the Russian government’s geopolitical aims through military force and non-military means. In addition to this, the paper explores the legitimacy challenges faced by the Wagner Group in terms of international law and norms of international relations, particularly in terms of state sovereignty, international conflict intervention and the legitimacy of private military operations. Through this analysis, the paper aims to provide insights into understanding and responding to the new challenges in the era of hybrid warfare.